ANALISIS EFISIENSI PENGGUNAAN ENERGI LISTRIK DI UPP LABORATORIUM TERPADU, SENTRA INOVASI, DAN LAYANAN RISET UNTIRTA - Muhammad Iqbal Nugraha; Didik Aribowo (Pusat Riset dan Inovasi Nasional, 2022)
In human life the use of electrical energy is very important and needed, but over time the use of its consumption is increasing. Therefore, it is necessary to save electricity consumption activities. This effort is known as energy conservation, one of which uses the energy audit method. Energy audit is to calculate the level of use or Energy Consumption Intensity (IKE) in the Untirta Integrated Laboratory Building whether it is efficient in the use of electrical energy. Collecting data related to electricity usage, building profiles, and observing lighting loads, air conditioning/air conditioning loads and other loads. The use of the IKE formula as a form of analyzing the data. The results of the study stated that the IKE value in the Untirta Integrated Laboratory Building was 38.019 kWh/m2, from this value it can be seen that the IKE is efficient. This is based on the parameters used by ASEAN-USAID of 240 kWh/m2. There is an addition in saving energy if in the future there are additional burdens such as laboratory equipment or electronic goods. These savings can be made by using LED lamps and replacing TL lamps or using lamps with a lower wattage than the previous lamp and can be done by reducing the duration of usage in consuming electrical energy.